Chapter The Revival of Cassiodorus' Variae in the High Middle Ages (10th-11th century) - Internullo, Dario (Reti Medievali E-Book, 2022)
This paper is based on a number of reuses of Cassiodorus' Variae that have been found in notarial documents written in Rome and Lazio between the tenth and eleventh century. Given that the manuscript tradition of the Variae becomes visible only from the twelfth-thirteenth centuries onwards, these reuses are a good starting point to reflect on a specific question: what were the practical and contingent motivations that, in Lazio, stimulated the intellectual elites to research and reuse the Variae? By following an alternative path to that of the manuscript evidence, it is thus possible better to identify the contexts of preservation, circulation, and practical use of the Variae underlying the more evident late medieval revival.